1993
DOI: 10.1128/iai.61.5.2082-2088.1993
|View full text |Cite
|
Sign up to set email alerts
|

Oral immunization with Toxoplasma gondii antigens in association with cholera toxin induces enhanced protective and cell-mediated immunity in C57BL/6 mice

Abstract: Following oral immunization of C57BLU6 mice with a Toxoplasma gondii sonicate (TSo) in association with either cholera toxin (CT) or CT B subunit, the T. gondii-specific in vitro proliferation of splenic T lymphocytes was determined. Cytokines produced by these T cells were then characterized. After oral challenge with T. gondii 76K cysts, the percentage of cumulative survival was assessed, as was the number of brain cysts in the mice which survived. The TSo-specific proliferation of splenic T lymphocytes was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…It has been suggested that CT enhances the immune response that is naturally induced by the antigen. Intranasal and/or oral administration of viral and bacterial antigens with CT preferentially induces Th1-like responses [29,41], whereas intranasal and/or oral administration of soluble protein antigens with CT promotes Th2-like immune responses [22,26]. Our results, however, are not consistent with this concept, since inhalation of BP with CT induced high levels of IgG2a antibodies, an isotype typical of a Th1 response (Fig.…”
contrasting
confidence: 56%
“…It has been suggested that CT enhances the immune response that is naturally induced by the antigen. Intranasal and/or oral administration of viral and bacterial antigens with CT preferentially induces Th1-like responses [29,41], whereas intranasal and/or oral administration of soluble protein antigens with CT promotes Th2-like immune responses [22,26]. Our results, however, are not consistent with this concept, since inhalation of BP with CT induced high levels of IgG2a antibodies, an isotype typical of a Th1 response (Fig.…”
contrasting
confidence: 56%
“…CT has been shown to induce Th2 responses after oral administration with soluble protein antigens; however, because CT is normally given with inactivated proteins, the extent to which CT can modify the helper T (Th) cell phenotype during the induction of strong Th1 responses, as occurs after infection with intracellular pathogens, is not clear. Furthermore, when given intranasally, or orally with less purified antigens, CT has been reported to induce Th1 and Th2 responses (8, 9). Therefore, we decided to test the ability of CT to modify Th1 responses in mice during systemic infection of BALB/c mice with a high dose of the ME-49 strain of T. gondii .…”
Section: Resultsmentioning
confidence: 99%
“…immunization with antigen conjugated to cholera toxin B subunit (CTB) plus cholera toxin (CT) as an adjuvant is more efficient than peroral immunization for inducing S-IgA antibodies in various secretions as well as for inducing circulating antibodies (45). CT is known to be a potent mucosal immunogen and adjuvant (4,7,10,21,22), but it is not feasible to use CT in human vaccines due to the highly toxic effects of the A1 subunit. The nontoxic CTB alone, however, seems to be ineffective as an adjuvant for intragastric (i.g.)…”
mentioning
confidence: 99%